M. Lillian Burke (1879-1952): Three Lost Chéticamp Carpets - Langille, Edward (Material Culture Review, 2014)
Abstract Mary Lillian Burke was an American artisan who, with the support and encouragement of Alexander Graham Bell’s daughters, Elsie Grosvenor and Marian Fairchild, created the Chéticamp hooked-rug cottage industry in the 1930s. From 1927 to 1940, Lillian Burke designed and marketed Chéticamp hooked rugs for leading New York decorators. Today, Lillian Burke’s creations are virtually unknown. Despite their commercial and artistic success, not one of the Chéticamp rugs Lillian Burke sold in New York City has ever been identified. In an effort to gain an appreciation of Lillian Burke’s creations, “Three Lost Chéticamp Carpets” examines contemporary press reports, Burke’s original designs, and photographs of three of her outstanding creations.